2018
DOI: 10.3389/fpls.2018.00605
|View full text |Cite
|
Sign up to set email alerts
|

LED Lighting – Modification of Growth, Metabolism, Yield and Flour Composition in Wheat by Spectral Quality and Intensity

Abstract: The use of light-emitting diode (LED) technology for plant cultivation under controlled environmental conditions can result in significant reductions in energy consumption. However, there is still a lack of detailed information on the lighting conditions required for optimal growth of different plant species and the effects of light intensity and spectral composition on plant metabolism and nutritional quality. In the present study, wheat plants were grown under six regimens designed to compare the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
86
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 57 publications
11
86
0
2
Order By: Relevance
“…However, it should be mentioned that the application of far-red light resulted in weak and thin leaves (data not shown). Inversely blue light inhibited the leaf expansion thus decreased the specific leaf area and increased the leaf thickness (it was observed, but not measured), similarly as was found at higher light intensity by us and by Meziane and Shipley (1999).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, it should be mentioned that the application of far-red light resulted in weak and thin leaves (data not shown). Inversely blue light inhibited the leaf expansion thus decreased the specific leaf area and increased the leaf thickness (it was observed, but not measured), similarly as was found at higher light intensity by us and by Meziane and Shipley (1999).…”
Section: Discussionsupporting
confidence: 80%
“…A relative overexcitation of PSII can results in an imbalance of photosynthetic electron transport between PS II and PS I, which can decrease the efficiency of the photosynthetic processes. In addition, the blue light-induced 'sun-type' characteristics of leaves was manifested also in the decrease of chlorophylls in spinach leaves, similarly as was found by Zhang et al (2016) and Monostori et al (2018). To ensure the optimal growth a fine balance between the blue and red ratio is necessary to provide equilibrated and efficient utilization of absorbed light energy between the PS II and PS I.…”
Section: Discussionsupporting
confidence: 63%
“…Furthermore, the ratio of red to blue light is also important for flowering 70 , which, in wheat, is induced earliest under pink light, where the ratio is around 1 (ref. 71 ). One feature of existing speed breeding systems is the use of LEDs to improve light quality and reduce operational costs 12,15 .…”
Section: Review Articlementioning
confidence: 99%
“…In addition, R film was beneficial to the accumulation of soluble proteins, which was consistent with the results of R light increasing soluble protein content in Phaseolus vulgaris 43 and wheat. 44 Anthocyanins are responsible for red or purple coloration in a variety of fruits, are major pigments in strawberry, and are beneficial to human health as antioxidant agents. 29,45 Zhang et al 28 found that R light and RB light induced the strawberry coloration earlier by increasing the content of total anthocyanins.…”
Section: Strawberry Chemical Properties Under Different Colored Filmsmentioning
confidence: 99%